PENGENALAN DASAR WEB DEVELOPMENT MENGGUNAKAN HTML DAN CSS PADA SISWA SMP PGRI 371 PONDOK AREN - Herwis Gultom; Faruq Syaifullah; Fiki Maipron; Hendrawan Wibowo; Ilham Nastiar; Muhammad Agil Syahdan; Muhammad Arifin Ilham; Muhammad Fatih Iqbal; Setyawan Dwi Prakoso (Abdi Jurnal Publikasi, 2024)
This report aims to provide an introduction to basic web development using HTML and CSS to PGRI 371 Pondok Aren Junior High School students. In today's digital era, an understanding of website creation is a very important skill. The method used in this research is a practical approach through training and workshops, where students are introduced to the basic concepts of HTML and CSS, as well as their application in creating simple web pages. The results of this activity showed an increase in students' understanding of web structure and design, as well as their ability to apply the knowledge gained to create simple web projects. Hopefully, this introduction can be the first step for students to further explore the world of web development and information technology. This research also provides recommendations for the development of a more integrated curriculum on digital technology in secondary schools.